Visual Outcome after Suprachoroidal Injection of Triamcinolone Acetate in Cystoid Macular Edema of Different Pathology - Muhammad Sajid Munir, Rabeya Rehman, Shahid Nazir, Nusrat Sharif, Mariam Zakia Chaudhari, Sheraz Saleem (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To analyze visual outcome after suprachoroidal injection of triamcinolone acetate in cystoids macular edema of different pathology. Study design: Prospective interventional study. Place and duration of study: Department of Ophthalmology, Niazi Medical & Dental College Sargodha from 1st July 2021 to 31st December 2021. Methodology: Fifty patients were suffering from uveitis (Intermediate uveitis) most common, diabetic macular edema resistant to other treatments like maximum anti-vascular endothelial growth factor injections, vascular occlusion disorders were included. All participants were followed-up at 1-week, 1-month 3 and 6 months and best corrected visual acuity and intraocular pressure was also recorded. All procedure done in the main operation theatre under full sterilization condition and consider it as a part of major procedure. Results: Females appeared to be more in number than to males. In mostly patients the cause of cystoids macular edema was uveitis (Intermediate type) (n=30) followed by vascular disorder (n=10). There was a significant improvement after treatment on visual acuity according to the given results. Conclusion: Common cause of cystoids macular edema in the present study was uveitis followed by vascular disorders. There was a significant improvement after treatment on visual acuity according to the given results. Most patients achieve good visual activity after treatment.